(untitled) (International Journal of Economics Management and Social Science, 2025)
The rapid development of information technology has encouraged micro, small, and medium enterprises (MSMEs) to adapt to digital-based marketing strategies. This study aims to analyze the influence of online marketing strategies implemented by Dimsum Kuy on consumer purchasing decisions. The strategies examined include social media marketing, digital content creation, online promotions, and collaboration with influencers. Data collection was conducted through a survey of 280 respondents who had purchased Dimsum Kuy online. The research instrument used a Likert-scale questionnaire, and the data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach to examine the relationships between variables, including direct and indirect influences through brand trust and purchase intention as mediating variables. The results show that all implemented online marketing strategies have a positive and significant influence on consumer purchasing decisions, both directly and through brand trust and purchase intention. Social media marketing has proven to be the most dominant factor in building trust and driving purchasing decisions. This study emphasizes the importance of optimizing digital channels and managing interactive consumer relationships as an effort to strengthen the competitive advantage of culinary MSMEs in the digital era. Recommendations are provided for businesses to improve the quality and frequency of interactions through social media and build brand credibility to strengthen customer loyalty.